Desmoplastic Small Round Cell Tumor of the Abdomen and Pelvis: Clinicopathological Characters of 12 Cases - Guangzhao Zhang; Guangjun Liu; Dahua Zhao; Xijun Cui; Gang Li (The Scientific World Journal)
Purpose. To study the clinical, radiological, and pathological characteristics of abdominal desmoplastic small round cell tumor (DSRCT) and investigate the optimal therapy modalities. Patients and Methods. A retrospective cohort study was performed on 12 abdominal DSRCT patients; all pathological, radiological, and prognostic data were analyzed. There were 3 patients (25%) with metastatic disease at presentation. In all 12 cases, 6 cases underwent operation and adjuvant chemotherapy (group 1, 6/12, 50%). The other 6 cases were diagnosed by fine needle aspiration or exploratory laparotomy biopsy (group 2, 6/12, 50%); all cases received four to six courses of multiple agents chemotherapy, respectively. Results. All cases were finally diagnosed as DSRCT pathologically. Among group 1, all cases underwent en bloc resection (2/6, 33%) or tumor debulking (4/6, 67%) and, following four courses of multiple agents chemotherapy, Kaplan-Meier analysis revealed that 3-year survival was 50% in group 1 versus 16.7% in group 2 (P<0.05). Gross tumor resection was highly significant in prolonging overall survival; patients with localized solitary lesion have a better prognosis, most likely due to increased feasibility of resection. Conclusions. DSRCT is a rare malignant tumor with poor prognosis. Surgical excision with combination chemotherapy as an adjunct is mandatory for nonmetastatic cases because these modalities used in isolation may have less impact.